Brain alarm by self-extracellular nucleic acids: from neuroinflammation to neurodegeneration - Kunze, Reiner; Fischer, Silvia; Marti, Hugo; Preissner, Klaus T. (Journal of biomedical science, 2023)
Neurological disorders such as stroke, multiple sclerosis, as well as the neurodegenerative diseases Parkinson's or Alzheimer's disease are accompanied or even powered by danger associated molecular patterns (DAMPs), defined as endogenous molecules released from stressed or damaged tissue. Besides protein-related DAMPs or “alarmins”, numerous nucleic acid DAMPs exist in body fluids, such as cell-free nuclear and mitochondrial DNA as well as different species of extracellular RNA, collectively termed as self-extracellular nucleic acids (SENAs). Among these, microRNA, long non-coding RNAs, circular RNAs and extracellular ribosomal RNA constitute the majority of RNA-based DAMPs. Upon tissue injury, necrosis or apoptosis, such SENAs are released from neuronal, immune and other cells predominantly in association with extracellular vesicles and may be translocated to target cells where they can induce intracellular regulatory pathways in gene transcription and translation. The majority of SENA-induced signaling reactions in the brain appear to be related to neuroinflammatory processes, often causally associated with the onset or progression of the respective disease. In this review, the impact of the diverse types of SENAs on neuroinflammatory and neurodegenerative diseases will be discussed. Based on the accumulating knowledge in this field, several specific antagonistic approaches are presented that could serve as therapeutic interventions to lower the pathological outcome of the indicated brain disorders.
Veröffentlicht: 07. August 2023
Gesehen am 27.09.2023